Analytical thinking skill profile and perception of pre service chemistry teachers in analytical chemistry learning. Issue 4 (February 2019) - Yulina, I K; Permanasari, A; Hernani, H; Setiawan, W
Abstract: Analytical Thinking is one of the Higher Order Thinking skills that is required in Analytical Chemistry learning. The purpose of this research is to portrait the profile of Analytical Thinking skills and perception of pre-service chemistry teachers towards learning. In this study, the aspects of analytical thinking skills are measured on using indicators developed by Marzano. The subjects in this study were 15 pre-service chemistry teachers, while the research data were collected through analytical thinking test instrument and questionnaire form. Further, the data obtained are were use as a basis for the development of analytical chemistry materials. The results showed that generally the analytical thinking skill of pre-service chemistry teacher is in the low category, with the average value of 63 (on 100 scale). Specifically, the tough stage from the highest are specifying, generalizing, analyzing errors, matching, and classifying. While the questionnaire results of pre service chemistry teacher toward Analytical Chemistry learning which got high, sufficient and low marks were the aspect of teaching materials; learning strategies, affective strategies, and cognitive strategies; the role of lecturers and material significance. Thus the role of lecturers and material significance is an aspect that must be developed to improve analytical thinking skills in the learning process.